Proceedings of the International Conference on Computer-Aided Design 2012
DOI: 10.1145/2429384.2429396
|View full text |Cite
|
Sign up to set email alerts
|

A polynomial time triple patterning algorithm for cell based row-structure layout

Abstract: As minimum feature size keeps shrinking, and the next generation lithography (e.g, EUV) further delays, double patterning lithography (DPL) has been widely recognized as a feasible lithography solution in 20nm technology node. However, as technology continues to scale to 14/10nm, DPL begins to show its limitations and usually generates too many undesirable stitches. Triple patterning lithography (TPL) is a natural extension of DPL to conquer the difficulties and achieve a stitch-free layout decomposition. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
80
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 7 publications
0
80
0
Order By: Relevance
“…In general, there exist two types of MPL, Litho-Etch-Litho-Etch (LELE) type and self-aligned type. LELE-type of MPL allows stitch insertions and two-dimensional patterns [27], [59], [70], [71], [77], but coloring and overlay compensation schemes become extremely complicated for triple patterning lithography and beyond [12], [15], [30], [38], [60], [73], [76], [81]. Self-aligned type of MPL can minimize electrical variations from overlay and line-edge-roughness but introduces complex coloring and line-end constraints [40], [42], [56].…”
Section: Introductionmentioning
confidence: 99%
“…In general, there exist two types of MPL, Litho-Etch-Litho-Etch (LELE) type and self-aligned type. LELE-type of MPL allows stitch insertions and two-dimensional patterns [27], [59], [70], [71], [77], but coloring and overlay compensation schemes become extremely complicated for triple patterning lithography and beyond [12], [15], [30], [38], [60], [73], [76], [81]. Self-aligned type of MPL can minimize electrical variations from overlay and line-edge-roughness but introduces complex coloring and line-end constraints [40], [42], [56].…”
Section: Introductionmentioning
confidence: 99%
“…Triple patterning lithography (TPL) is one of the most promising techniques in the 14 nm logic node and beyond. In order to realize a target pattern, various types of techniques including design for manufacturability, such as LELE type double patterning lithograph [1][2][3][4][5][6][7], LELELE type TPL [8][9][10][11][12][13][14][15][16][17][18], LELECUT type TPL [19], and side wall process [20], are used in addition to a basic litho-etch process with optimized mask. These techniques are summarized in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…LELELE type TPL technology [8][9][10][11][12][13][14][15][16][17][18] in which litho-etch process is repeated three times is often discussed in literature. However, it suffers from native conflict and overlay problems.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of research efforts have been devoted to TPL [4], [11], [18], [19], [22] [3], [13], [15]- [17]. Bei Yu et al showed that the general TPL decomposition problem is NP-hard, and further proposed an ILP based algorithm to compute legal TPL solutions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results verify that the problem can be solved very efficiently with the proposed algorithm. Superior locally balanced decompositions are achieved compared with the previous approach in [19].…”
mentioning
confidence: 99%